ANALISIS KEMAMPUAN ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED UNTUK MENGUKUR KINERJA KEUANGAN PT INDOCEMENT TUNGGAL PRAKARSA, TBK - Nur Fahmi; Sutardi Sutardi (Universitas Pamulang, 2017)
The purpose of this study to analyze the financial performance of PT. Indocement Tunggal Prakasa, Tbk by Economic Value Added method and Market Value Added method. The research method used by the writer is descriptive quantitative. The results showed that the value of EVA and MVA PT. Indocement Tunggal Prakasa, Tbk has fluctuated and reached positive value during 2011-2014. EVA and MVA positively indicates that the company is able to generate economic value added and create wealth for shareholders